His dark materials. The complete second season [videorecording (DVD)] - Keen, Dafne, 2005-; Wilson, Amir, 2004-; Wilson, Ruth, 1982-; Stamp, Terence; Miranda, Lin-Manuel, 1980-; Pullman, Philip, 1946- (Warner Bros. Home Entertainment, 2021)
In Season 2, Lyra follows Lord Asriel into the mysterious abandoned city Cittagazze while Mrs. Coulter continues to search for her.